To Solution of Contact Problem for Elastic Half-Strip - S. V. Bosakov (Наука и техника)
Contact problems for elastic stripes have been well studied and published in domestic scientific literature. This is partly due to the fact that normative documents on the foundation structure it is recommended to use this elastic foundation model for simulation of a “structure – foundation – soil foundation” system. Two variants of boundary conditions at the contact between a half-strip and a rigid non-deformable base are usually considered. The first boundary condition nullifies the vertical displacements and tangential stresses, the second one nullifies vertical and horizontal displacements. Contact problems for an elastic half-strip are much less investigated. The paper considers this contact problem when the first boundary condition for zeroing of vertical displacements and tangential stresses at the contact of a half-strip with a rigid, nondeformable base. When performing calculations in the traditional formulation without taking into account tangential stresses in the contact zone, the Zhemochkin method has been used, which reduces the solution of the contact problem of solid mechanics to the solution of a statically indeterminate problem by the mixed method of structural mechanics. Therefore, at first, we have found the displacements of the upper edge of the half-strip from the unit load uniformly distributed over the edge section. The resulting expression is used to compose a system of equations for the Zhemochkin method. The case of translational displacement of the die has been considered, and the graph of contact stress distribution under the die's sole has been given in the paper.